Bridging Language and Heritage: Exploring Teachers’ Use of Digital Applications in Teaching English With Dayak Ngaju Cultural Content - Bannus, Dedy; Emeral (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Culture-Based Teaching (CBT) enhances students’ linguistic competence and cultural awareness, and recent advances in digital applications offer new opportunities for embedding indigenous content into EFL pedagogy. Despite the proliferation of digital tools in language classrooms, little research has examined how teachers integrate Dayak Ngaju cultural materials into digitally assisted English instruction. This exploratory qualitative study investigates the digital applications EFL teachers use, the language skills they target, and the challenges they encounter when teaching English with Dayak Ngaju cultural content. Semi-structured interviews were conducted with six senior high school teachers from two regencies in Central Kalimantan Province, Indonesia, and the transcripts were analysed using thematic analysis in NVivo 12 and Transcribe. The results reveal that YouTube and Canva are the most frequently employed applications, with local folklore serving as the primary Dayak Ngaju content. Speaking and writing emerge as the main skills teachers aim to develop through these digital resources. However, the study also highlights several obstacles, including unstable internet connectivity, insufficient teacher training, technical issues, school restrictions, and a lack of suitable Dayak Ngaju materials for the senior high school level. This study suggests that educators should be equipped with targeted training and accessible digital resources to effectively incorporate Dayak Ngaju cultural content into English instruction, enhancing students' language skills and cultural awareness.